Improvement of Lactic Acid Production from Cassava by Streptococcus bovis Using Two-Stages Membrane Bioreactor - Dwi Yuwono, Suripto; Widiarto, Sonny; Hadi, Sutopo; Kokugan, Takao (Asian Journal of Chemistry, 2014)
The investigation of improvement for lactic acid production from fresh cassava roots by Streptococcus bovis using two-stages membrane bioreactor with purging was performed to increase the concentration and productivity of the lactic acid. The result showed that by the use of two-stages membrane bioreactor, the productivity and concentration of lactic acid were 5.03 and 50 g/L, respectively which were obtained at dilution rate of 0.25 h-1 and 30 g/L feeding sugar concentration. Based on the data obtained, it is shown that the two-stages membrane bioreactor system was very effective and efficient and it could be potentially used for the production of lactic acid from fresh cassava roots by S. bovis.